Agile Principles for Projects Within the Fashion industry - Shahir, Sara (My University, 2017)
This thesis is a study about if traditional project management is suitable for all sorts of companies and their projects. The work examines (i) the current project life cycle that the company encounters; (ii) some examples of Modern Project Management (MPM) techniques and how they might change project workflows (iii) whether, if changes are adopted would this make any difference, and (iv) what the opportunities as well as the difficulties faced in their work would be. There is no doubt that there is strong competition within the fashion industry currently, and that companies need to compete hard to make their product(s) the optimum choice for the clients. A literature review was carried out to find how project management theories relate to the fashion industry, the project management approaches that are actually used in the industry, and newer (MPM-type) approaches that could, potentially be beneficial. In terms of empirical data, the project life cycle of Amethyst London was investigated and examined against the theoretical findings from the literature review. This comparison between theory and practice revealed that Amethyst London, without their knowledge are working according Traditional Project Management and it is working well for them at the moment. There will always be room for development and improvement, which the company are aiming for. Also, the size of the company is at the moment plays a great role in the research due to the limitations of employees and their resources. At the end of the study, under Chapter 7, Section 7.3, there will be a recommendation presented aimed for the company and their organisation structure.
Keywords: Samhällsbyggnadsteknik; Civil Engineering